PENGHINDARAN RISIKO, DIVERSIFIKASI PENDAPATAN DAN EFISIENSI INTERMEDIASI BANK DI INDONESIA - Bang Jessica Santiyano; Kim Sung Suk (Universitas Bunda Mulia, 2017)
This study aims to examine the effect of bank-specific factors, market structure and macroeconomic to intermediation efficiency of bank as measured by the spread. The data used as many as 99 conventional commercial banks in Indonesia from 2004 to 2013. Panel data estimation method uses the fixed effect model. Results showed that risk averse has positive effects on spread. Income diversification has negative effect on the spread. Other results show that bad loans and liquidity have negative effect on spread. While the operating costs, the market concentration, economic growth, and inflation has negativve effect on spread.Keywords: bank efficiency, risk averse, income diversification